2019
DOI: 10.1016/j.biopsych.2019.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Nociceptin Receptors Are Related to Resilience and Recovery in College Women Who Have Experienced Sexual Violence: Therapeutic Implications for Posttraumatic Stress Disorder

Abstract: Post-traumatic stress disorder (PTSD) is a stress disorder that develops in only some individuals following a traumatic event. Data suggest that a substantial fraction of women recover after sexual violence. Thus, the investigation of stress and anti-stress neuropeptides in this sample has the potential to inform the neurochemistry of resilience following trauma. Nociceptin is an anti-stress neuropeptide in the brain that promotes resilience in animal models of PTSD. METHODS: [ 11 C]NOP-1A PET was used to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 61 publications
(84 reference statements)
4
10
0
Order By: Relevance
“…On the contrary, its blockage prevented this phenomenon, contributing to increased resilience to stress. These findings are in agreement with recent studies that showed an association between increased NOP receptor signaling and vulnerability to stress (Der-Avakian et al, 2017; Narendran et al, 2019). Furthermore, depression is a gateway to drug addiction (Gómez-Coronado et al, 2018).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…On the contrary, its blockage prevented this phenomenon, contributing to increased resilience to stress. These findings are in agreement with recent studies that showed an association between increased NOP receptor signaling and vulnerability to stress (Der-Avakian et al, 2017; Narendran et al, 2019). Furthermore, depression is a gateway to drug addiction (Gómez-Coronado et al, 2018).…”
Section: Discussionsupporting
confidence: 94%
“…This pivotal study, for the first time, linked the overexpression of the endogenous N/OFQ system with a depressive-related phenotype. Recently, midbrain and cerebellum NOP receptor binding, measured by positron emission tomography, was positively correlated with post-traumatic stress disorder (PTSD) symptoms in women who have experienced sexual violence (Narendran et al, 2019). This study reinforces the view that lower NOP receptor signaling is related to resilience and recovery in PTSD.…”
Section: Introductionsupporting
confidence: 65%
“…Other peptides which have been shown to influence resilience and stress responses, though at a much more preliminary level of evidence, include the endogenous opioid family of enkephalins ( Nam et al, 2019 ), orexin ( Staton et al, 2018 ; Summers et al, 2020 ), nociceptin ( Narendran et al, 2019 ), somatostatin ( Stengel and Tache, 2017 ), and galanin ( Sciolino et al, 2015 ). These peptides have been shown to enhance resilience in animal models during experimental stress-inducing procedures, and to influence other molecules of key importance in brain resilience, such as BDNF.…”
Section: Key Research Areas In the Neurobiology Of Resilience And Thementioning
confidence: 99%
“…Of the many endogenous opioids, β-endorphin—which may be raised by social music-making—has been implicated in resilience, stress, and PTSD (Bali et al, 2015 ) as has the neuropeptide nociceptin (Tollefson et al, 2017 ; Narendran et al, 2019 ). Nociceptin receptor polymorphisms have been linked to the severity of PTSD, but unlike β-endorphin, no relationship to music has been examined.…”
Section: The Links Between Oxytocin and Musicmentioning
confidence: 99%